Global Warming Risk Perceptions in India - Thaker J; Smith N; Leiserowitz A (John Wiley and Sons, Ltd on behalf of the Society for Risk Analysis)
Few studies have focused on global warming risk perceptions among people in poor and developing countries, who are disproportionately impacted by climate change. This analysis conducts a comprehensive assessment of global warming risk perceptions in India using a national sample survey. Consistent with cultural theory, egalitarianism was positively associated with global warming risk perceptions. In addition, perceived vulnerability and resilience to extreme weather events were also two of the strongest factors associated with global warming risk perceptions. While worry was positively associated with risk perceptions, it accounted for only a small proportion of the variance, unlike studies in developed countries. Finally, the study also collected global warming affective images. The most common responses were “don’t know” or “can’t say” (25%), followed by “pollution” (21%), “heat” (20%), and “nature” (16%). The study finds that the predictors of global warming risk perceptions among the Indian public are both similar and different than those in developed countries, which has important implications for climate change communication in India.
Thaker, Jagadish, Smith, Nicholas, and Leiserowitz, Anthony ; 2020; Global warming risk perceptions in India; "Published in Risk Analysis" ; http://dx.doi.org/10.1111/risa.13574
Keywords: Affective imagery; cultural worldviews; India; perceived vulnerability and resilience; risk perceptions